The Autotelic Self in Jamaica Kincaid’s at the Bottom of the River - Okeugo, Oluchi Chris; Onyinye, Obioha Jane (Journal of English Language and Literature (ISSN: 2368-2132), 2020)
Kincaid’s fiction focused on the Caribbean dislocation and displacement which relates to racism, colonialism, and trans-culturality with little or no consideration of the role of the autotelic self in contesting these cultural forces. This study examines the extent to which the Julia Kristeva’s principles of language and subject formation and Mihaly Csikszentmihalyi’s principles of autotelic personality could intersect with this autotelic self. Using the postcolonial feminist literary theory and the Csikszentmihalyi’s principles of autotelic personality, it seeks to ascertain the degree to which Jamaica Kincaid’s selected fiction violate or adhere to Kristeva’s principles of language and subject formation and Csikszentmihalyi’s principles of autotelic personality. It applied the cultural and novel of the Julia Kristeva’s principles and the Csikszentmihalyi’s principles to Kincaid’s selected poetic novella. The study depicts that Kincaid in the selected novella violates the Kristeva’s principles as well both in the same cadre.